Ø¯ÙˆØ± Ø§Ù„ÙˆØ§Ù„Ø¯Ø© Ø¹Ù„Ù‰ Ø±ØºØ¨Ø© Ø§Ù„Ø·Ù„Ø¨Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†ÙŠØª Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¯Ø§Ø± Ø§Ù„ÙØ§Ø¦Ø²ÙŠÙ† Ø§Ù„Ø³Ù„ÙÙŠØ© Ø¬ØªØ§Ùƒ ØºÙŠØ§Ù… Ù…ÙˆØ¬ÙˆØ§Ø±Ù†Ùˆ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ - Atana Masâ€™ilatul Bariroh; Mohammad Arif Setyabudi (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
In this article, the purpose of this study is to find out the role of mother to students' interest in learning Arabic through online learning. This research uses qualitative research that is sourced data from observations, interviews and documentation. As for the results of his research, there are many parents (mothers) who are not aware of his role as a mother and also as a teacher for his children who always care for, educate, and teach children school lessons, in this case Arabic lessons through online learning. Most students find it difficult to understand arabic lessons delivered through online learning, this is why students' learning interest decreases, therefore the need for awareness from a mother to always guide and motivate children to learn Arabic through online learning.